Current status of targeted microbubbles in diagnostic molecular imaging of pancreatic cancer - Natacha Jugniot; Rakesh Bam; Emmanuelle J. Meuillet; Evan C. Unger; Ramasamy Paulmurugan (Bioengineering & Translational Medicine, 2021)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is often associated with a poor prognosis due to silent onset, resistance to therapies, and rapid spreading. Most patients are ineligible for curable surgery as they present with advanced disease at the time of diagnosis. Present diagnostic methods relying on anatomical changes have various limitations including difficulty to discriminate between benign and malignant conditions, invasiveness, the ambiguity of imaging results, or the inability to detect molecular biomarkers of PDAC initiation and progression. Therefore, new imaging technologies with high sensitivity and specificity are critically needed for accurately detecting PDAC and noninvasively characterizing molecular features driving its pathogenesis. Contrast enhanced targeted ultrasound (CETUS) is an upcoming molecular imaging modality that specifically addresses these issues. Unlike anatomical imaging modalities such as CT and MRI, molecular imaging using CETUS is promising for early and accurate detection of PDAC. The use of molecularly targeted microbubbles that bind to neovascular targets can enhance the ultrasound signal specifically from malignant PDAC tissues. This review discusses the current state of diagnostic imaging modalities for pancreatic cancer and places a special focus on ultrasound targeted‐microbubble technology together with its clinical translatability for PDAC detection.